ECOLOGICAL ANALYSIS OF LITERATURE SHORT STORY “HARIMAU BELANG” - Nuramila Nuramila (Journal of Language, Literature and Teaching, 2020)
Nature is often not just a setting for a fictional story in a literary work, but can also be the main theme in a literary work. The existence of the link between nature and literature raises a concept of ecological problems in literature among literary critics. The term eco-criticism (ecocriticism) is used as a term regarding the concept of literary criticism related to nature and the environment. One of the writers who explored nature in literary works was Guntur Alam. One of his works is the short story